Teaching for Religious Literacy - Gallagher, Eugene V. (Teaching theology and religion, 2009)
Stephen Prothero's Religious Literacy makes a strong case that minimal religious literacy is an essential requirement for contemporary U. S. citizens. He argues further that high schools and colleges should offer required courses in the study of religion in order to help students reach that baseline literacy. Beyond the general recommendation that such courses focus on biblical literacy and the history of Christianity, however, Prothero does not sketch out his proposal for teaching religious literacy. This essay argues that in addition to providing factual knowledge, teaching for religious literacy needs to involve sustained attention to how religious people use that factual information to orient themselves in the world, express their individual and group self-understanding, and give their lives direction and meaning. Such attention to the dynamics of religious life can also help students understand why human beings have persisted in this mode of behavior.